Youngstown's 'Ghost'? Memory, Identity, and Deindustrialization. (7th January 2014) - Rhodes, James
Abstract This article considers the highly contested and contradictory uses of the industrial past that continue to animate questions of place-based identity in the wake of large-scale deindustrialization. Drawing on media accounts as well as qualitative interviews with city residents, the representations surrounding Youngstown, Ohio's former middleweight boxing champion, Kelly Pavlik, and his asserted relationships to the city are considered. It is argued that through the various depictions of Pavlik, we see how deindustrialization has led to a more complex interaction of space and time—rather than marking a material and symbolic break from the era in which heavy industry dominated the city and its sense of identity—as aspects of the past are alternately disavowed, recovered, rearticulated, and reconstructed in relation to shifting economic, social, and cultural contexts.